TRANSFORMASI DIGITAL PEMBELAJARAN PAI: PELUANG DAN TANTANGAN DI ERA GLOBALISASI - Muzdalena; Zaitun; Windayani (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
Digital transformation has become a global phenomenon that significantly influences educational practices, including Islamic Religious Education (IRE). Advances in information technology provide opportunities for pedagogical innovation, broader access to Islamic learning resources, and the strengthening of IRE’s role in promoting religious moderation in the era of globalization. However, digitalization also presents complex pedagogical, structural, and ethical challenges. This study aims to analyze comprehensively the opportunities and challenges of digital transformation in IRE learning within the context of globalization. Employing a qualitative approach with a library research design, the study critically examines recent scholarly literature related to Islamic education and digital learning. The findings indicate that digital transformation in IRE learning has the potential to enhance educational quality and relevance when supported by teachers’ digital competence, adaptive curricula, and a strong value-oriented framework. Nevertheless, challenges such as uneven digital readiness, technological disparities, reduced depth of learning, and ethical concerns remain significant obstacles. The study concludes that the success of digital transformation in IRE learning depends on the ability of Islamic educational institutions to position technology as a pedagogical tool oriented toward character formation, Islamic values, and religious moderation.